Green tea extracts attenuate doxorubicin-induced spermatogenic disorders in conjunction with higher telomerase activity in mice - Sato, Kenji (Springer US, 2010)
PURPOSE: The aim of this study was to investigate the protective effect of green tea extracts against doxorubicin-induced damage in the mouse testes correlating with telomerase activity. METHODS: Green tea extracts were administered orally. Doxorubicin was coadministered intraperitoneally. These testes were evaluated histologically and the telomerase activity was analyzed. Additional immunostaining was carried out. RESULTS: Both the sperm density and sperm motility were significantly increased in green tea extracts coadministration groups as compared to the doxorubicin-treated groups. By histological analysis, germ cell damage was greatly attenuated by green tea extracts coadministration. Telomerase activity significantly increased in association with the coadministration of green tea extracts as compared to that of doxorubicin-only groups. In all groups, human telomerase reverse transcriptase signals were mainly observed in the spermatocytes and spermatids. CONCLUSIONS: These findings suggest that green tea extracts exert protective effects against doxorubicin-induced spermatogenic disorders in conjunction with higher telomerase activity levels.